A polysomal ribonuclease involved in the destabilization of albumin mRNA is a novel member of the peroxidase gene family. - Chernokalskaya, E (1998)
We have purified an approximately 60 kDa endoribonuclease from Xenopus liver polysomes with properties expected for a messenger RNase involved in the estrogen-regulated destabilization of serum protein mRNAs (Dompenciel et al., 1995, J Biol Chem 270:6108-6118). The present report describes the cloning of this protein and its identification as a novel member of the peroxidase gene family. This novel enzyme, named polysomal RNase 1, or PMR-1 has 57% sequence identity with myeloperoxidase, and like that protein, appears to be processed from a larger precursor. Unlike myeloperoxidase, however, PMR-1 lacks N-linked oligosaccharide, heme, and peroxidase activity. Western blot and immunoprecipitation experiments using epitope-specific antibodies to the derived protein sequence confirm the identity of the cloned cDNA to the protein originally isolated from polysomes. The 80 kDa pre-PMR-1 expressed in a recombinant baculovirus was not processed to the 60 kDa form in Sf9 cells and lacks RNase activity. However, the baculovirus-expressed mature 60-kDa form of the enzyme has RNase activity. The recombinant protein is an endonuclease that shows selectivity for albumin versus ferritin mRNA. While it does not cleave at consensus APyrUGA elements, recombinant PMR-1 generates the same minor cleavage products from albumin mRNA as PMR-1 purified from liver. Finally, we show estrogen induces only a small increase in the amount of PMR-1. This result is consistent with earlier data suggesting estrogen activates mRNA decay through a posttranslational pathway.